A new approach on the development of a nonlinear model for micro pelton turbines - Özdemir, Mahmut Temel; Orhan, Ahmet (My University, 2015)
In this study, a new approach that is closer to the real turbine without abandoning the advantages of nonlinear modeling simplicity compromising the simplicity of the nonlinear model is proposed. The purpose of the study is to contribute to making theoretical studies of microhydroelectric power plants (MHPPs) more realistic. Studies on their control, especially frequency control, have increased with the expansion of grid-connected power plants. However, some problems have occurred when converting simulation studies of the frequency control to practical studies. The reasons for these problems are that the systems cannot be modeled completely. In this study, first, the nonlinear model equations of a Pelton turbine are primarily constituted. The efficiency curve of the turbine is then obtained experimentally and added to the nonlinear model. The simulation results are compared with the data obtained from the prototype MHPP with a Pelton turbine developed in the laboratory. Finally, it is seen that the proposed method is successful. Thus, with the help of the proposed method, theoretical studies that researchers do can be easily converted into practical applications.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Nonlinear hydraulic turbine model; Micro-Pelton turbine; Microhydro power plant